2016
DOI: 10.4140/tcp.n.2016.215
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Direct-to-Consumer Advertising and the Older Adult Population

Abstract: Direct-to-consumer advertising (DTCA) has become a prominent feature of our society and reaches many consumers through their televisions, radios, and computer screens. In 2004, the average United States citizen was exposed to more than 16 hours of DTCA per year, and the number of hours has steadily increased. Drug advertising is a multi-billion dollar business for pharmaceutical manufacturers and affects public perception of medications, both prescription and over-the counter. Studies have shown advertisements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A key consumer of DTCA are older adults, as they are more likely to be impacted by the diseases specified in pharmaceutical DTCA. 17 In fact, older age is associated with increased exposure to DTCA. 18 Studies have observed mixed positive and negative perceptions of DTCA among older adults.…”
Section: Subpopulation Experiencesmentioning
confidence: 99%
See 2 more Smart Citations
“…A key consumer of DTCA are older adults, as they are more likely to be impacted by the diseases specified in pharmaceutical DTCA. 17 In fact, older age is associated with increased exposure to DTCA. 18 Studies have observed mixed positive and negative perceptions of DTCA among older adults.…”
Section: Subpopulation Experiencesmentioning
confidence: 99%
“…Moreover, DTCA has led to increased knowledge and conversations with providers among older adults. 17 Conversely, older adults also have reported that DTCA has limited or missing information, which has led to inappropriate conclusions being drawn for therapy. 14,19 In addition, women are more often targeted by DTCA than men.…”
Section: Subpopulation Experiencesmentioning
confidence: 99%
See 1 more Smart Citation